(untitled) (Baghdad Science Journal, 2022)
Obesity is a risk factor for a number of chronic conditions. Obesity is clinically defined using the body mass index (BMI) as weight in kg divided by (height)2 in m2 correlated with obesity. Currently, genetic markers of obesity are being studied. This study focused on the association between the angiotensin II receptor AGTR1 gene (A1166C) and fat mass and obesity-associated protein also known as alpha-ketoglutarate-dependent dioxygenase (FTO) (rs9939609) in obese children and adolescents patients in Rostov region, Russia. Five-hundreds of Russian nationality child and adolescent were recruited for the obesity-control studies. The relationship between the A1166C polymorphism of the AGTR1 gene in 300 children and adolescents included as the unhealthy group, compared with healthy group of 200 participants were investigated. Genotyping of A1166C polymorphisms of the AGTR1 rs5186 gene was performed using PCR allele-specific primers. Polymorphisms of the AGTR1 A1166C (rs5186) genes in donor DNA samples were typed by the electrophoretic method using commercial test systems from the Lytech research and production company. The relationship between obesity and AGTR1 gene polymorphism (A1166C) was not established between the obesity and control groups in terms of the frequency of occurrence of the CC genotype (P = 1.000) and (OR 1.05; 95% CI (0.53 – 2.10)) and the C allele (P = 0.942) and (OR 1.01; 95% CI (0.76 – 1.35)). However, in the occurrence of frequency genotype of AA (P = 0.003; OR 0.57; 95% CI (0.39 – 0.82)) and T (P = 0.006) of allele and (OR 1.44; 95% CI (1.11 – 1.87)) the rs9939609 of the FTO gene were revealed differences (P <0.05) between patients and control groups. The association between genotypes obesity risk was indicated, and a significant relationship was shown between the occurrence of obesity with the FTO rs9939609 polymorphism.